FV 10. Nerve conduction studies in CIDP at first diagnosis and during disease course: a cross-sectional study in a large cohort of patients. Issue 8 (August 2021) - Bulut, Y.; Grüter, T.; Kordes, A.; Athanasopoulos, D.; Motte, J.; Fisse, A.L.; Otto, S.; Schneider-Gold, C.; Yoon, M.S.; Gold, R.; Pitarokoili, K.
Abstract : Background. Nerve conduction studies represent the gold standard in the diagnosis of chronic inflammatory demyelinating polyneuropathy (CIDP) and play a central role in the EFNS/PNS criteria. However, the highly extensive examination protocol of those criteria and the question how to further monitor are relevant problems in daily medical practice. Hence, the aim of this cross-sectional study is to establish a practical and applicable strategy a) conducting the EFNS/PNS criteria and b) monitoring disease related disability in a large cohort of CIDP patients. Methods. As part of a prospective cohort study, we conducted a bilateral neurographic examination of the median nerve (mot.+sens.), ulnar nerve (mot.+sens.), radial nerve (sens.), tibial nerve (mot.), peroneal nerve (mot.+sens.), and sural nerve (sens.) in 95 CIDP patients. The EFNS/PNS criteria were applied on the collected neurographic data and compared with the INCAT overall disability sum score (INCAT-ODSS) and INCAT sensory score (ISS) to quantify disease disabilities. Results. In total, 95 CIDP patients (f:m 1:3.32; mean age 59±12y; 52% atypical CIDP; mean disease duration 74±60 months) were recruited, thereof 25 at initial diagnosis. All patients fulfilled the electrophysiological EFNS/PNS diagnosis criteria for CIDP. At initial diagnosis, the median nerve met the single parameters of the EFNS/PNS criteria most frequently with 72%, followed by the tibial nerve with 66%, ulnar nerve with 46%, and peroneal nerve with 22%. In total, the criterion of prolonged distal cMAP duration was met most frequently (32%), followed by an abnormal temporal dispersion (16%) and absence of F-waves (13%). However, we identified axonal damage as the parameter related with clinical disability ( p  < 0.001), not demyelination. Thus, distal cMAP and sNAP amplitudes could be identified as predictive markers of disability, especially in the upper limbs (related to INCAT-ODSS: ulnar nerve: R2 = 0.219; median nerve: R2 = 0.099; peroneal nerve: R2 = 0.044; tibial nerve: R2 = 0.034; related to ISS: ulnar nerve: R2 = 0.118; radial nerve: R2 = 0.112; sural nerve: R2 = 0.096; peroneal nerve: R2 = 0.084; median nerve: R2 = 0.082). The neurographic parameters of the upper limbs might relate to a greater extent to the total disability than those of the lower limbs, since nerves of the lower limbs have already shown extensive axonal damage (71% of distal cMAP amplitudes of the peroneal nerve and 45% of the tibial nerve <1 mV). Conclusions. Although the majority of CIDP patients reveal symptoms predominant of the legs, the examination of the upper limbs has proven to be essential for both initial diagnosis and disease monitoring, underlining CIDP as a systemic disease. Especially the determination of the distal cMAP duration was a sensitive parameter in the detection of CIDP. The total disability is largely determined by the degree of axonal damage. Therefore, neuroprotection should have an important additional role in the CIDP therapy in the future.